Mammalian Polycomb-Like Pcl2/Mtf2 Is a Novel Regulatory Component of PRC2 That Can Differentially Modulate Polycomb Activity both at the Hox Gene Cluster and at Cdkn2a Genes - Li, Xiangzhi (American Society for Microbiology (ASM), 2011)
The Polycomb group of proteins forms at least two distinct complexes designated the Polycomb repressive complex-1 (PRC1) and PRC2. These complexes cooperate to mediate transcriptional repression of their target genes, including the Hox gene cluster and the Cdkn2a genes. Mammalian Polycomb-like gene Pcl2/Mtf2 is expressed as four different isoforms, and the longest one contains a Tudor domain and two plant homeodomain (PHD) fingers. Pcl2 forms a complex with PRC2 and binds to Hox genes in a PRC2-dependent manner. We show that Pcl2 is a functional component of PRC2 and is required for PRC2-mediated Hox repression. Pcl2, however, exhibits a profound synergistic effect on PRC1-mediated Hox repression, which is not accompanied by major alterations in the local trimethylation of histone H3 at lysine 27 (H3K27me3) or PRC1 deposition. Pcl2 therefore functions in collaboration with both PRC2 and PRC1 to repress Hox gene expression during axial development. Paradoxically, in embryonic fibroblasts, Pcl2 is shown to activate the expression of Cdkn2a and promote cellular senescence, presumably by suppressing the catalytic activity of PRC2 locally. Taken together, we show that Pcl2 differentially regulates Polycomb-mediated repression of Hox and Cdkn2a genes. We therefore propose a novel role for Pcl2 to modify functional engagement of PRC2 and PRC1, which could be modulated by sensing cellular circumstances.